Digital inclusive finance and the development of sports industry: An empirical study from the perspective of upgrading the living level of rural residents - Huang, Hui; Zhang, Yunxuan (Frontiers in Environmental Science, 2022)
With the development of science and technology, digital inclusive finance has been widely used in various fields and has promoted the development of industrial structures. The development of the sports industry is a realistic option for improving public health problems and sustainable economic development. In this study, we understand the impact of digital inclusion finance on the sports industry from the perspective of upgrading the living standards of rural residents. Using relevant data from some domestic provinces in China from 2015-2019 as a sample, we explore the relationship between digital inclusion finance and the sports industry and analyse whether the living standards of rural residents play a mediating role. The study finds that: firstly, digital inclusive finance has a facilitating effect on the development of the sports industry. Secondly, digital inclusive finance can create a scale effect by increasing rural per capita disposable income, which in turn promotes the development of the sports industry. Thirdly, digital inclusive finance will use its digital and precise characteristics to precisely improve the consumption structure of rural residents, thus promoting the development of the sports industry. The study enriches the research related to digital economy represented by digital inclusive finance, and has important practical guidance significance for the development of China's sports industry.